2013
DOI: 10.1149/05002.0183ecst
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Interfacial Oxygen Transport Resistance for a PEMFC Cathode Incorporating Water Droplet Coverage

Abstract: The transport resistance of oxygen in a PEMFC flow field and gas diffusion layer interface was numerically investigated in a 3D model. This model solved for the convection of air and the diffusion of oxygen in the air in a single flow field channel. The interfacial oxygen transport resistance was expressed with the Sherwood number. For a dry channel, the numerically obtained Sherwood number was validated by the relationship between Nusselt and Sherwood numbers through the Lewis number. Following the validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…The mass transfer between the GDL and the channel in PEFCs has been analytically studied by Koz and Kandlikar. 35,36 Based on their numerical simulation, they obtained Sh = 3.36 for a flow channel whose geometry was 0.7 mm width and 0.4 mm depth, which agrees well with the value of 3.279 calculated using the Nusselt-Sherwood (Nu-Sh) analogy. 35 In addition, when no water droplets were present in the channel, their results clearly showed that Sh was steady at 3.36 regardless of change in flow velocity in the range from 1.59 to 15.89 m s −1 .…”
Section: Sample Notation Cp Cp+m M Sglsupporting
confidence: 63%
“…The mass transfer between the GDL and the channel in PEFCs has been analytically studied by Koz and Kandlikar. 35,36 Based on their numerical simulation, they obtained Sh = 3.36 for a flow channel whose geometry was 0.7 mm width and 0.4 mm depth, which agrees well with the value of 3.279 calculated using the Nusselt-Sherwood (Nu-Sh) analogy. 35 In addition, when no water droplets were present in the channel, their results clearly showed that Sh was steady at 3.36 regardless of change in flow velocity in the range from 1.59 to 15.89 m s −1 .…”
Section: Sample Notation Cp Cp+m M Sglsupporting
confidence: 63%
“…This Sh FD is significantly lower than the ones previously recommended: Sh FD =5.274 [42] (value readjusted for the characteristic length of hydraulic diameter), 6.0 [43], and 5.411 [44]. Moreover, it was shown that local Sh can be larger than Sh FD downstream of the droplet [41]. As a result, a single droplet was found to decrease the interfacial O 2 resistance, a finding that is in agreement with the results of Chen et al [16].…”
Section: Nomenclaturementioning
confidence: 56%
“…In a later numerical study by Koz and Kandlikar [45], single, two and multiple droplet cases were simulated over a more refined parametric range compared to their previous work [41]. Two and multiple droplet simulations revealed the effect of droplet spacing on Sh and how Sh varied at each consecutive droplet,…”
Section: Nomenclaturementioning
confidence: 98%
See 1 more Smart Citation
“…In the fully developed region, Sh can be assumed constant, ~3.66 [50]. Koz and Kandlikar found Sh to be 3.36 using 3D simulation [52].…”
Section: Phase Change (Condensation) At the Channel Surfacementioning
confidence: 99%